The effects of granulocyte-colony stimulating factor on chronic liver disease: a meta-analysis - Pei Shi; Jianguo Zhang; Min Wu; Ting Zheng; An Liang; Zhilong Wen; Xiaoping Wu (Journal of Infection in Developing Countries)
Introduction: The clinical application of granulocyte-colony stimulating factor on chronic liver disease is still controversial. The study aimed to evaluate the effects of granulocyte-colony stimulating factor on chronic liver disease.